Theranostic targeting of CUB domain containing protein 1 (CDCP1) in pancreatic cancer - Moroz, Anna (Clin Cancer Res, 2020)
PURPOSE: The recent emergence of radioligand therapies for cancer treatment has increased enthusiasm for developing new theranostic strategies coupling both imaging and cytotoxicity in the same entity. In this study, we evaluated if CUB domain containing protein 1 (CDCP1), a single pass transmembrane protein highly overexpressed in diverse human cancers, might be a target for cancer theranostics. EXPERIMENTAL DESIGN: The ectodomain of CDCP1 was targeted using radiolabeled forms of 4A06, a potent and specific recombinant human antibody that we developed. Imaging and antitumor assessment studies were performed in animal models of pancreatic cancer, including two PDX models we developed for this study. For antitumor assessment studies, the endpoints were death due to tumor volume >3000 mm(3) or ≥20% loss in body weight. Specific tracer binding or antitumor effects were assessed with an unpaired, two-tailed Student’s t test and survival advantages were assessed with a log rank (Mantel Cox) test. Differences at the 95% confidence level were interpreted to be significant. RESULTS: (89)Zr-4A06 detected a broad dynamic range of full length or cleaved CDCP1 expression on seven human pancreatic cancer tumors (n = 4/tumor). Treating mice with single or fractionated doses of (177)Lu-4A06 significantly reduced pancreatic cancer tumor volume compared to mice receiving vehicle or unlabeled 4A06 (n = 8, P<0.01). A single dose of (225)Ac-4A06 also inhibited tumor growth, although the effect was less profound compared to (177)Lu-4A06 (n = 8, P<0.01). A significant survival advantage was imparted by (225)Ac-4A06 (HR = 2.56, P <0.05). CONCLUSIONS: These data establish that CDCP1 can be exploited for theranostics, a finding with widespread implications given its breadth of overexpression in cancer.